2019
DOI: 10.2140/paa.2019.1.385
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of edge states in perturbed honeycomb structures

Abstract: This paper is a mathematical analysis of conduction effects at interfaces between insulators. Motivated by Haldane-Raghu [HR08, RH08], we continue the study of a linear PDE initiated in Fefferman-Lee- FLW16b]. This PDE is induced by a continuous honeycomb Schrödinger operator with a line defect.This operator exhibits remarkable connections between topology and spectral theory. It has essential spectral gaps about the Dirac point energies of the honeycomb background. In a perturbative regime, the authors of [FL… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 108 publications
(103 reference statements)
0
16
0
Order By: Relevance
“…We proved an analogous statement in [Dr18b,Lemma 4.3] for different values of the parameters ξ and z. Here we require |ξ − ξ | ≤ ε 0 and z ∈ ∂D µ ± δ (ξ), r δ (ξ) instead of |ξ −ξ | ≤ δ 1/3 and z ∈ D E , θ ·r δ (ξ) for some θ ∈ (0, 1).…”
Section: Bulk Indexmentioning
confidence: 59%
See 4 more Smart Citations
“…We proved an analogous statement in [Dr18b,Lemma 4.3] for different values of the parameters ξ and z. Here we require |ξ − ξ | ≤ ε 0 and z ∈ ∂D µ ± δ (ξ), r δ (ξ) instead of |ξ −ξ | ≤ δ 1/3 and z ∈ D E , θ ·r δ (ξ) for some θ ∈ (0, 1).…”
Section: Bulk Indexmentioning
confidence: 59%
“…The associated time-harmonic waves propagate in opposite directions. In [Dr18b] we proved that all edge states take this form, and showed that the corresponding spectral flow vanishes. This agrees with the bulk-edge correspondence.…”
Section: Bulk Indexmentioning
confidence: 79%
See 3 more Smart Citations